PROLEGOMENA TO A NEW CRIMINAL TRIAL PROCEDURE IN POLAND FOLLOWING THE AMENDMENT OF THE CODE OF CRIMINAL PROCEDURE OF 27.09.2013: FROM INQUISITORIAL TOWARDS ADVERSARIAL PROCEDURE OF WITNESS EXAMINATION IN CRIMINAL TRIALS - BEDNAREK, Grażyna Anna (Comparative Legilinguistics, 2015)
The purpose of this paper is twofold. Firstly, it introduces the transformations, which the criminal trial procedure in Poland will undergo following the amendment of the Code of Criminal Procedure of 27 September 2013. Secondly, it explains the consequences that the altered criminal law will have on Polish courtroom discourse. The paper comprises three major parts. It commences with the demonstration of the inquisitorial procedure of witness examination in criminal trials as investigated, described, and expounded by Bednarek (2014), prior to the amendment of criminal law in Poland. Subsequently, it presents the criticism of the inquisitorial criminal trial by the representatives of academia and legal practitioners in Poland, and explains the reasons for the transformation of the inquisitorial criminal trial into an adversarial one. Finally, it demonstrates the new regulations of the Code of Criminal Procedure pertaining to the criminal trial and establishes what effects they will have on Polish courtroom discourse. The paper ends with concluding remarks emphasizing the pressing need for novel and thorough investigations of the language used by judges, attorneys for the prosecution and attorneys for the defense in criminal trials in Poland following the amendment of the criminal law. At the time when this paper is being written the study of courtroom discourse conducted by Bednarek (2014) is the only investigation of talk in interaction in the milieu of Polish courts that focuses on the modus operandi of witness examination from the point of view of linguistics.